RISK MANAGEMENT ANALYSIS AT ABC BANK IN KEDIRI, INDONESIA - Silvi Rushanti Widodo; Heribertus Budi Santoso (Center for Study and Journal Management FTI UMI, 2023)
Risk management is a very important thing to do in a company. Small and large scale company will never avoid risk.. This study aims to identify risks, measure risks and analyze and evaluate the risks faced by ABC bank in Kediri City, Indonesia. This study uses risk management analysis with a qualitative descriptive method. The stages in risk measurement research are as follows risk identification, risk assessment, and risk response. The results of interviews with the director of risk management and employees of bank ABC can be seen the types of risks that are likely to occur in bank ABC are credit risk, market risk, liquidity risk, operational risk, compliance risk, legal risk, reputation risk, strategic risk. Credit risk has the highest level of risk, namely with cases of more than 9 customers per year with a case value of more than 450-500 million per year. Next is the market risk which has a moderate risk level with a case value between 250 million and 350 million per year. Risk management in credit and market risk is with all employees must have a strong credit analysis for prospective customers who apply for credit to the bank, the Manager must ensure that the amount of credit received by the customer is in accordance with the predetermined ceiling, the Manager monitors the distribution of credit to be on target, and etc.